2009
DOI: 10.1016/j.ijid.2008.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Association between Mycobacterium avium subsp. paratuberculosis DNA in blood and cellular and humoral immune response in inflammatory bowel disease patients and controls

Abstract: These results indicate the existence of immune responses and treatment interactions with MAP that strongly support an etiological role of this agent in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 26 publications
3
34
1
Order By: Relevance
“…It is currently recognized as one of the main diseases of dairy cattle in industrialized countries and results in substantial financial losses every year for the dairy industry (Hasonova and Pavlik, 2006). Beyond this financial damage, bovine MAP infection may pose a public health risk, as MAP has been linked to Crohn's disease in humans (Juste et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is currently recognized as one of the main diseases of dairy cattle in industrialized countries and results in substantial financial losses every year for the dairy industry (Hasonova and Pavlik, 2006). Beyond this financial damage, bovine MAP infection may pose a public health risk, as MAP has been linked to Crohn's disease in humans (Juste et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In 2009 Juste et al from Spain, employed the same methods, nested PCR for IS900, on buffy coat, and reported 15% of CD patients, 19/124, to be positive, 19% of UC patients, 17/90, and 43%, 34/80, of healthy controls. 59 Kirkwood et al tested both peripheral blood mononuclear cells (PBMC) and fresh biopsies, using a similar nested PCR for IS 900. 20 These were from pediatric cases of CD that had never been treated.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…The nested PCR technique has proved to be popular and accurate, with recent studies using this method to identify MAP in IBD patients more frequently than in control patients. 77,78 Another recent study using the nested IS900 PCR method demonstrated the presence of MAP DNA in children with CD at early onset, 79 which is the earliest identification of MAP DNA in a patient to date. There have now been several studies that have shown the presence of MAP DNA in adult blood samples 73,80,81 and in diseased tissue.…”
Section: Mycobacterium Avium Subspecies Para-tuberculosis and Crohn'smentioning
confidence: 99%